Implementación de un chatbot para recolección de posibles casos de covid-19 mediante una página web - Erazo Navarrete, Wilmer Stalin (2020)
Today the evolution of artificial intelligence is already more present today, with the resolution to automate various processes within any type of organization, company or institution, artificial intelligence allows us to develop a Chatbot (robot) that has the ability to simulate the conversation a human needs. Artificial intelligence has the ability to acquire and apply learned knowledge, the same amount of information as human intelligence. Currently, there are several creations in chatbot that allow automating recurring processes, can decrease the response times of an activity, guarantee the availability of the service and / or omit the presence of a person. In the health area, it is essential to have an assistant who knows how to give information at any time of the day, and even more so when it is crossed by global health crises. The present research work is oriented to the implementation of a Chatbot based on artificial Intelligence to help in the detection of possible cases of COVID-19, within the institutional platform and that counts as support to predict possible contagions.